Automatic mouse feeding system - Akid Haris; Suraya Abdul Sani; Ainol Azifa Mohd Faik; Nico Arnoly Nawan; Corinna Au Li Mei (2021)
The Automatic Mice Feeding System (AMFS) is an automated routine base mice feeding technology design which is meant to be used in common animal house laboratory found in many research institutes. The design of AMFS comes from the use of recycle materials such as oil containers, bicycle chains, tubes, and gears. AMFS functions through a connection of its manual design with an online software program that allows users to access the program from anywhere with an internet connection. Different from other “fill it and leave it” design on the market, AMFS let its user to determine the amount of feed and the time of feeding as desired. By doing so, researchers will no longer be required to visit the animal house for feeding purposes which can potentially benefit important factors such as time, cost and energy. The world as we known today is moving towards automation of systems, yet there are still some laboratory procedures such as mice feeding that are still done traditionally and manually which sometimes proves to be tedious. AMFS can help change this situation and bring in new and innovative method in taking care and feeding laboratory mice.